On discount rates for economic evaluations in global health. Issue 1 (18th October 2019) - Haacker, Markus; Hallett, Timothy B; Atun, Rifat
Abstract: Choices on discount rates have important implications for the outcomes of economic evaluations of health interventions and policies. In global health, such evaluations typically apply a discount rate of 3% for health outcomes and costs, mirroring guidance developed for high-income countries, notably the USA. The article investigates the suitability of these guidelines for global health [i.e. with a focus on low- and middle-income countries (LMICs)] and seeks to identify best practice. Our analysis builds on an overview of the academic literature on discounting in health evaluations, existing academic or government-related guidelines on discounting, a review on discount rates applied in economic evaluations in global health, and cross-country macroeconomic data. The social discount rate generally applied in global health of 3% annually is inconsistent with rates of economic growth experienced outside the most advanced economies. For low- and lower-middle-income countries, a discount rate of at least 5% is more appropriate, and one around 4% for upper-middle-income countries. Alternative approaches—e.g. motivated by the returns to alternative investments or by the cost of financing—could usefully be applied, dependent on policy context. The current practise could lead to systematic bias towards over-valuing the future costs and health benefits of interventions. For health economic evaluations in global health, guidelines on discounting need to be adapted to take account of the different economic contexts of LMICs.